The Influence of Employee Mental Health on Workplace Performance:A Human Resource Management Perspective - M Ananda; Rehan AditiaB (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The significance of employee mental health within the framework of human resource management is gaining attention due to its direct impact on work performance and organizational productivity. Increasing workplace demands, rapid changes, and psychological pressures contribute to mental health challenges such as stress, anxiety, and burnout among employees. Objective : This study aims to analyze how employee mental health influences work performance and organizational outcomes, while also identifying effective HR management strategies to support employees’ mental well-being. Research Methods/ Implementation Methods : This research uses a qualitative descriptive method through literature review, exploring journal articles, organizational reports, and best practice guidelines published from 2020 onwards, focusing on HR management and workplace mental health. Results : Findings show that poor mental health among employees leads to decreased productivity, higher absenteeism, and reduced job satisfaction. Organizational support in the form of mental health policies, Employee Assistance Programs (EAP), and flexible work arrangements directly correlate with improved performance, lower stress, and increased loyalty. Conclusion/Lesson Learned : Comprehensive mental health management within organizations is essential. HR should implement proactive support systems, offer psychological assistance, and foster a supportive work environment. These strategies are proven to enhance employee resilience, productivity, and long-term organizational success, without sacrificing well-being